Enhancing Emergency Preparedness in Mass Gatherings through Crowd Simulation and Cascading Effect Analysis - Li, Jiayao; Congès, Aurélie; Bénaben, Frédérick (Proceedings of the International ISCRAM Conference, 2026)
In collaboration with French firefighters (SDIS 62), this study aims to enhance emergency preparedness for mass gatherings through a comprehensive framework integrating crowd simulation and cascading effect analysis. The proposed framework enables the modeling of various emergency scenarios and the evaluation of potential response strategies. The framework’s application is demonstrated through a case study of a major music festival. Furthermore, a proposed simulation of high-urgency medical scenarios using what-if analyses is explored to optimize response times. The integration of advanced communication technologies, such as drones and telemedicine, is highlighted for its potential to transform emergency response effectiveness. The findings of the study imply that such a framework can refine proactive planning for large-scale events and improve overall readiness to respond to emergencies.